A Survey of Banks in Ghana's Credit Risk Management Practices - Dabi, Rowland Seyram Koku; Nugraha, Nugraha; Disman, Disman; Sari, Maya (Image : Jurnal Riset Manajemen, 2023)
In recent times, banks and other financial institutions that lend money to customers have placed a high priority on credit risk management. To manage credit risk, banks employ customer evaluation systems, loan size restrictions, credit checks, flexible loan repayment plans, and fines Hence, the present study focuses on  the credit risk management practices used in banks, to identify the internal control measures used in mitigating  credit risk in banks and to examine the challenges faced in implementing credit risk management practices. The Ordinal Logistic Regression(OLR) was used to identify the relationships between the response variables, e.g. management support, credit risk identification, internal control measuers and credit risk management surveys. The independent variables were calculated on an ordered, 5-point Linear scale for the responding participants. In this study,  log lit function was chosen, that demonstrated the model appropriateness. One of the main finding is that in banks, credit management risk is reduced when managers implement and adhere to responsible credit risk management procedures, viable client appraisal credit management system, regular credit checks, flexible credit repayment systems to encourage and improve loan repayment, were highly significant with the respondents’ positive initiative amidst credit risk management practices in banks.